Simulasi Metaverse Konser Musik Virtual Berbasis Roblox - Akhmad Rifky Rinaldi; Susan Dian Purnamasari (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Metaverse as a form of technological advancement has become a hot topic of discussion at worldwide. Metaverse is a technology that can create a three-dimensional virtual world by utilizing modern technology, where users can interact as if they are in a real-world through three-dimensional avatars. In Metaverse, users can do many things as usual, such as gathering with friends, working, learning, playing, shopping, experimenting, creating, and so on. Almost all physical activities and social interactions can be done in Metaverse. However, research on Metaverse is currently limited to knowledge and theory, and there is not much research discussing the detailed and actual form of Metaverse itself. Therefore, as a first step in building Metaverse, this research will focus on creating a virtual music concert as a simulation of the Metaverse world using the Roblox platform with the aim of creating a Metaverse simulation with a virtual music concert theme, providing references related to the appearance, environment, and atmosphere that can be used in Metaverse, as well as introducing features and user flow when watching a virtual music concert.